Impacts of maltene on the wettability and adhesion properties of rejuvenated asphalt binder - Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim; Haryati, Yaacob; Mohd Khairul Idham, Mohd Satar (Springer, 2021)
In recent years, the use of reclaimed asphalt pavement (RAP) has gained much attention and is widely accepted. However, the rejuvenating agents which are usually used to reduce the rigidity of the aged asphalt are subjected to diverse climate circumstances. The present work used maltene as a rejuvenator to investigate several measurements regarding stripping failure. The evaluation of wettability and work of adhesion (WA) was assessed using the sessile drop method. Meanwhile, asphalt and asphalt-water aggregate systems were tested for acid and water resistance using chemical and water immersion tests. Next, atomic force microscopy (AFM) was used to evaluate the changes in the microstructures of the asphalt binders. The experimental results revealed that the ideal percentages of maltene which should be added to 30% and 50% aged asphalt were 8% and 16%, respectively. Meanwhile, the wettability, WA and resistance to stripping difered depending on the percentage of aged asphalt in the blend. However, the inclusion of maltene has improved samples containing high percentages of aged asphalt. On the other hand, the resistance to boiling water containing acid decreased slightly with the addition of maltene. Nevertheless, all the rejuvenated samples exhibited better results than virgin asphalt. Moreover, the AFM results were in line with the observations, suggesting the suitability of maltene for the functional application of pavement.